Ukrepi za omilitev posledic epidemije covid-19 na področju delovnih razmerij - Mašera, Damjan (Delavci in delodajalci, 2020)
Labour legislation provides the employer with several possibilities for flexible organisation of the work process. The intervention measures of the state in relation to covid-19 have either supplemented the already existent institutes (reimbursement of the salary compensation by the State), upgraded it (higher salary compensation) or created a new institute (shorter working hours due to the consequences of Covid-19). The paper presents four content strands: the use of working time, the type and place of work, the (non-)provision of work and intervention measures.
Keywords: covid-19 epidemic; delovna razmerja; delovni čas; epidemija covid-19; intervention measures; interventni ukrepi; labor relations; nadomestilo plače; wage compensation; working hours